DA'WAH AMIDST RELIGIOUS AND CULTURAL DIFFERENCES (STUDY OF Q.S. AL-HUJURAT:13) - Ardila, Bela (QAULAN: Journal of Islamic Communication, 2021)
The Unitary State of the Republic of Indonesia is a country that has many cultures, this is evidenced by the Indonesian slogan "Bhinneka Tunggal Ika" which means "different but still one thing". In a variety of cultures, humans need interaction with other humans, namely what is known as the word "communication". Peace in the midst of cultural differences is the application of Allah's orders in the teachings of Islam. Created from a man and woman and made humans into nations and tribes so that humans know each other to be devoted to Allah SWT. Contextual interpretation of the Quran and considering the socio-historical context in interpreting a text is so urgent and important. This is directly related to the spirit of the Koran, where Muslims must always learn and develop a number of knowledge by involving the text of the Qur'an on the one hand and dialogue with reality on the other. Da'wah bil-hal and verbally become a milestone of success for community harmony in Cempaka Putih Village, Jelutung District, Jambi City, Jambi Province. Keywords: Intercultural Communication, Contextual of the Quran, Da'wah